The Role of Women in Advancing Islamic Education in West Sumatra: An Analytical Study of Chadijah Ismail - Rahmadi, Rahmadi; Syahri, M.; Hidayati, Abna; Riadi, Slamet (STAI YAPTIP Simpang Empat Pasaman Barat Indonesia in collaboration with International Islamic Studies Development and Research Center (IISDRC), 2023)
History records that women in West Sumatra have a big role in advancing education, especially Islamic education, among these women is Chadijah Ismail, who is known as an academic figure who has succeeded in educating the Muslim community, she even left behind her work in the form of establishing an Islamic religious institution which still exists today. This research aims to explore Chadijah Ismail's role in advancing Islamic education for Muslim communities in West Sumatra, especially in Pasaman Barat, Indonesia. This research uses qualitative methods with the type of character study (long life history), data sources were taken through individual interviews with ten informants consisting of key informants (Chadijah Ismail), close family, religious and community leaders, the academic community, alumni and students of the STAI YAPTIP Simpang Empat Pasaman Barat, all Informants are selected using techniques purposive sampling. Besides that, data is also taken from real work in the form of analysis documents. All data was analyzed using interactive techniques by Milles and Huberman. Research findings show Chadijah Ismail's three roles in advancing Islamic education, these three roles are as an academic, educator, and leader in college. First; as an academic, he is actively involved as a lecturer, researcher, and author of books that have influenced the style and variety of thoughts on the practice of Islamic education. Second; relatedly, as an educator, he founded Al-Quran educational institutions, early childhood educational institutionss, and even established modern Islamic boarding schools, the benefits of which have been felt by the community. Third; related to the role as a leader of a higher education institution (leadership), he founded this institution in 1989 it was started at tarbiyah High School, and now it has developed into an Islamic educational institution with many students and alumni of almost five thousand people, this institution is one of the private Islamic universities with the largest number of students in West Sumatra. Referring to these findings, it can be seen that Chadijah Ismail is indisputably one of the women who has had a big impact on Muslim society. Of course, the figure of Chadijah Ismail needs to be used as an example for generations of Muslims, especially women in West Sumatra.